ANALYSIS OF FARMERS' VALUE CHAIN IN IMPROVING THE QUALITY OF COFFEE EXPORT PRODUCTS - Fadli Hazmi; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (RADJA PUBLIKA, 2024)
Control of coffee plantations in Indonesia is dominated by small farmers who have not yet implemented the value chain. This research aims to analyze coffee farmers in implementing the value chain at each stage of cultivation and post-harvest processing activities and find out how the value chain is implemented to improve product quality. This type of research is qualitative research with a grounded theory approach. The informants in this research were five informants from several villages in Mandailing Natal Regency, North Sumatra. Data collection uses participatory observation, in-depth interviews, and documentation. The research results show that the majority of coffee farmers in Mandailing Natal Regency do not carry out cultivation and post-harvest processing to increase production and quality, so they do not get added value to the product because farmers do not receive assistance in carrying out these activities. Farmers need assistance in implementing the value chain, namely assistance with cultivation activities by carrying out conceptual planting, using superior seeds, routine fertilization, routine pruning, and harvesting red fruit and assistance with post-harvest processing by carrying out fruit sorting, standard grinding, clean washing, and standard drying. Assistance provided to farmers can be provided through exporters, farmer groups and related institutions who continuously increase the added value of coffee products.